Light‐Driven Self‐Oscillating Behavior of Liquid‐Crystalline Networks Triggered by Dynamic Isomerization of Molecular Motors. (17th June 2021) - Sun, Jian; Hu, Wei; Zhang, Lanying; Lan, Ruochen; Yang, Huai; Yang, Deng‐Ke
Abstract: The self‐sustainable dynamic movement of soft actuators represents a continuous motion upon constant stimulus to achieve its great potential in emerging photoresponsive applications from self‐propelling machines, artificial robots to advanced biomimetic devices. Conversion of dynamic isomerization of molecular motors and switches into macroscopic self‐oscillation of soft materials is highly attractive but challenging. In this study, an overcrowded alkene motor with trifunctional acrylate groups is designed and synthesized, and its photoisomerization can be achieved in the liquid‐crystalline networks. Furthermore, the photodynamic storage modulus can be mainly modulated by the dynamic stable–unstable isomerization of the molecular motor upon UV exposure. Thus, the light‐driven self‐oscillating behavior from chaotic to regular movement can be performed based on the photodynamic mechanical balance of the micro‐oscillating modulus of the polymer network triggered by the dynamic reconfiguration of the motor. The results pave the way for inspirations in the development of advanced photoactive functional architectures and biomimetic actuators. Abstract : Light‐driven self‐oscillating behavior from chaotic to regular motion is demonstrated in liquid‐crystalline networks loaded with molecular motors. Based on the photodynamic mechanical anisotropy mainly modulated by the reversible stable–unstable isomerization of a molecular motor, the oscillating frequency and deflection amplitude are compatible with the concentration of motor, the UV intensity, and the anisotropic modulus of the polymer network.